The Relationship Between Nutritional Status And Sleep Disorders Among Students of Senior High School X In Gamping Subdistrict, Sleman Regency - Bambang Edi Susyanto (International Journal of Science and Environment (IJSE), 2025)
Sleep disturbance is a prevalent health problem among high school students and may be influenced by their nutritional status. Disrupted sleep patterns can negatively affect academic performance, concentration, and overall physical well-being. This study aimed to examine the association between nutritional status and sleep disturbance among students of SMA X in Gamping District, Sleman Regency. A cross-sectional study was conducted involving 105 participants. Nutritional status was determined using Body Mass Index (BMI) based on WHO criteria, while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using descriptive statistics and the Chi-Square test. Results showed that 84.8% of students experienced sleep disturbances, with the highest prevalence observed among those categorized as overweight and obese (100%). The Chi-Square analysis indicated a significant association between nutritional status and sleep disturbance (χ² = 7.32; p = 0.031), whereas no significant relationship was found between gender and sleep disturbance (p = 0.201). The findings highlight that nutritional status plays a significant role in sleep quality among adolescents. Promoting balanced nutrition and healthy sleep behaviors may contribute to improved health outcomes and academic performance in students.